Peran Remaja Masjid dalam Meningkatkan Kemakmuran Masjid Sabilil Jannah di Kampung Doy, Banda Aceh - Hizbun Al-Faiyadh bin Sulaiman; Fadhilah (Jurnal Riset dan Pengabdian Masyarakat, 2022)
The study aims to know how the mosque youth's contribution to increase mosque prosperity and to know what obstacles the youth are facing during the youth activities of the sabili jannah mosque. The research method used is qualitative research methods with a phenomenon approach to get data relating to the mosque's youth and its constriction in masijid sabilil jannah. Where as data analysis in the field with models miles and Huberman, that is, the data collection is repeated and complete. As for the results of his research, that is: (1) the mosque youth had a chance to vacuum, whether it was his vision and mission or his work program. (2) the role of mosque youth is not effective because most members are inactive after their fellow members' first meeting. (3) because the less-active member of the mosque youth index helps the sabilil jannah mosque BKM, not even the mosque's youth work program is launched. (4) the lack of awareness of mosque adolescent members who are less active toward the importance of organization has thus affected other members' being hampered. (5) the preoccupation of youth with their work has led to the hindering organization of mosque youth. (6) the obstacles facing the youth of the mosque, in general, are due to lectures and covid-19. (7) the image of the sabilil jannah mosque goes down because of the inactivity of the mosque's youth.